UJI KANDUNGAN ANTIOKSIDAN DAN FLAVONOID EKSTRAK BIJI TANAMAN MAHONI (Swietenia mahagoni) - Siti Aminatuz Zuhria; Afiq Masruri; Dyah Ayu Sri Hartanti (Universitas Tribhuwana Tunggadewi, 2023)
Mahogany plants have many benefits, one of which is the seeds of the mahogany tree. The content of flavonoids in mahogany seeds is high and used as antioxidants. This study aimed to know antioxidant and flavonoid content of mahogany seed extract.The extraction method used in this study is the maceration method and antioxidant test using the DPPH method. DPPH solution was prepared by dissolving DPPH powder dissolved in ethanol p.a. Antioxidant inhibition test with several variations of concentration and inhibition values, namely 7500 ppm at 76.41%, 3750 ppm at 67.07%, 1875 ppm at 42.54%, 937.5 ppm at 22.13% and 468.75 ppm by 9.95%. The highest inhibition was at a concentration of 7500 ppm with an inhibition value of 76.41% and the lowest at a concentration of 468.75 ppm with an inhibition value of 9.95%. The result showed that mahogany seeds have high antioxidant levels with an IC50 value of 64.07 mg/ml. The content of flavonoids in mahogany seeds showed high levels with a value of 17.7 QE with an extract concentration of 100 ppm.